Subchronic exposure to Chlorpyrifos, Carbofuran, and Cypermethrin increase sciatic nerve damage and degeneration in adolescent rats - Muhammad Ihwan Narwanto; Muhammad Haikal Supriyadi; Desie Dwi Wisudanti (Universitas Muhammadiyah Surabaya, 2023)
Several types of pesticides that are often used are chlorpyrifos (organophosphate), carbofuran (carbamate), and cypermethrin (pyrethroid). Pesticides can kill pests but also can cause toxic effects on humans when exposed. One of the adverse effects of pesticide exposure is a disturbance in the peripheral nervous system. Age is an essential factor in peripheral nerve damage. Nerve injury is one of the most common injuries in children and adolescents and is estimated at 10% to 15% of all exceptional unit cases. However, the outcome of peripheral nerve injury is known better in subjects who sustain the injury at a younger age. This study aims to determine the subchronic exposure effect of chlorpyrifos, carbofuran, and cypermethrin to sciatic nerve histopathology in juvenile rats. This study used 30 male Wistar rats (Rattus norvegicus) which were divided into 5 groups, normal group (N), control group (K), chlorpyrifos group (P1), carbofuran group (P2) and cypermethrin group (P3). Subcutaneous injection of pesticides was carried out for 21 days. Rats were sacrificed using the cervical dislocation method, and the right sciatic nerve was taken for histopathological observation. Assessment of the degree of ischiatic nerve histopathological damage is using the Jensen et al., (2018) method. Data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney test. This study showed a significantly increased degree of histopathological damage in the chlorpyrifos group, carbofuran group, and cypermethrin group compared to the control group and the normal group (p<0.05). It can be concluded that exposure to chlorpyrifos, carbofuran, and cypermethrin pesticides increased damage and degeneration of the ischiadicus nerve in juvenile rats.